Coronavirus Surveillance in a Pediatric Population in Jordan From 2010 to 2013: A Prospective Viral Surveillance Study. Issue 1 (January 2021) - Haddadin, Zaid; Chappell, James; McHenry, Rendie; Pulido, Claudia Guevara; Rahman, Herdi; Gu, Wenying; Rankin, Danielle A.; Talj, Rana; Howard, Leigh M.; Williams, John V.; Faouri, Samir; Shehabi, Asem; et al.
Abstract : Background: Human coronaviruses (HCoVs) are a significant cause of acute respiratory illness (ARI) in children; however, the role of HCoVs in ARI among hospitalized children in the Middle East is not well defined. Methods: Children under 2 years admitted with fever and/or respiratory symptoms were enrolled from 2010 to 2013 in Amman, Jordan. Nasal/throat swabs were collected and stored for testing. Demographic and clinical characteristics were collected through parent/guardian interviews and medical chart abstractions. Prior stored specimens were tested for HCoVs (HKU1, OC43, 229E and NL63) by qRT-PCR. Results: Of the 3168 children enrolled, 6.7% were HCoVs-positive. Among HCoV-positive children, the median age was 3.8 (1.9–8.4) months, 59% were male, 14% were premature, 11% had underlying medical conditions and 76% had viral-codetection. The most common presenting symptoms were cough, fever, wheezing and shortness of breath. HCoVs were detected year-round, peaking in winter-spring months. Overall, 56%, 22%, 13% and 6% were OC43, NL63, HKU1 and 229E, respectively. There was no difference in disease severity between the species, except higher intensive care unit admission frequency in NL63-positive subjects. Conclusions: HCoVs were detected in around 7% of children enrolled in our study. Despite HCoV detection in children with ARI with highest peaks in respiratory seasons, the actual burden and pathogenic role of HCoVs in ARI merits further evaluation given the high frequency of viral codetection.